Comparison of a direct and indirect population pharmacodynamic model: Application to recombinant human Erythropoietin in athletes - Bressolle, F.; Audran, M.; Gareau, R.; Pham, T.-N.; Gomeni, R. (Journal of Pharmacokinetics and Biopharmaceutics, 1997)
Basic physiologic indirect response models have been proposed to account for the pharmacodynamics of drugs that act by way of inhibition or stimulation of the production or loss of endogenous substances or mediators. In this work, these models were applied to account for the effects of recombinant human erythropoietin (rHuEpo) in man. Indeed, rHuEpo induces a delayed increase of serum soluble transferrin receptors (sTfr) and a delayed decrease in ferritin (fr) concentrations. The purpose of the present study was to compare two pharmacodynamic approaches to relate serum erythropoietin (Epo) concentrations to the effect of rHuEpo on sTfr, and fr, the indirect effect and the effect compartment models. However, due to the average lag lime of about 50 hr between the first intake of rHuEpo and the onset of the measurable effects, a delay function was incorporated into the indirect response models to describe the relationship between the Epo plasma concentrations and the endogenous receptors or mediators affected by the drug and responsible for the effects on sTfr and fr. There are no real differences in the descriptive features of the two models used. For these reasons, the indirect model seems more appropriate because it supplies a possible mechanistic interpretation of the physiological process.